Endpoint temperature, cooking method, and marbling degree have different effects on Warner-Bratzler shear force of beef strip loin, bottom round, and brisket muscles - E. Obuz; J.W. Stephens; J.P. Grobbel; T.M. Loughin; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 2004)
Our objective was to determine the effects of endpoint temperature, cooking method, and marbling on Warner-Bratzler shear force (WBSF; an objective method for determining tenderness) of three beef muscles. Eighteen subprimals of a muscle containing low content of connective tissue, longissimus lumborum (strip loin), and two muscles containing a high content of connective tissue, biceps femoris (bottom round) and deep pectoralis (brisket), were selected from USDA Select and Choice (Certified Angus Beef) carcasses. After 14 days of aging, subprimals were frozen, fabricated into steaks, and stored frozen until cooking. Steaks were assigned to one of two cooking methods, the Magikitch'n® electric belt grill (a rapid conduction method) or a water bath (a slower, convection method); and one of nine endpoint cooking temperatures, 104, 113, 122, 131, 140, 149, 158, 167, or 176°F. According to WBSF results, optimum tenderness for the strip loin occurred around 131°F. Higher marbling protected tenderness at higher endpoint temperatures. Tenderness increased in bottom round and brisket muscles as endpoint temperature increased from 104 to 140°F, then tenderness decreased as endpoint temperature rose from 149 to 176°F. Endpoint temperature was the only significant factor affecting bottom round tenderness. Steaks cooked in the water bath had higher WBSF and, therefore, were less tender than those cooked on the belt grill. This was true for both the strip loin and brisket. The effect of increasing endpoint temperature on WBSF of the strip loin was different than for the bottom round and brisket.
Keywords: Cattlemen& #x27; s Day; 2004; Kansas Agricultural Experiment Station contribution; no. 04-242-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 923; Beef; Endpoint temperature; Warner-Bratzler shear force; Cooking method; Marbling degree